Motives for joining trade union - Svärd, Sven-Erik (Uppsala University, 2014)
In this study the respondent were asked about the own and the parents trade union affiliation, trade unions present at the place of work, reason for joining the trade union and attitude toward people not affiliated with trade unions. Other questions dealt with union meeting attendance, union introduction and help from the trade union.

Undersökningen innehåller frågor om respondentens utbildning och nuvarande arbete; föräldrarnas fackliga aktivitet; fackliga organisationer på arbetsplatsen; uppdragsvillighet; anslutning; skäl till facklig anslutning; inställning till fackligt oorganiserade; facklig introduktion; fackliga möten; hjälp från facklig organisation.
Motiv för facklig anslutning
Keywords: occupations; yrken; trade union membership; medlemskap i fackförening; trade union officials; fackföreningsfunktionärer; labour and employment; arbete och sysselsättning; autonomy at work; autonomi i arbetet; conditions of employment; anställningsvillkor; job security; anställningstrygghet; status in employment; tjänsteställning; trade unions; fackföreningar; working conditions; arbetsförhållanden; hours of work; arbetstid; Labour relations/conflict; Förhållande/konflikter mellan arbetsmarknadens parter; Social Sciences; Samhällsvetenskap